Immediate Pain Relief in Patients with Trigeminal Neuralgia Following Microvascular Decompression - Muhammad Aqeel Natt, Muhammad Imran Khan, Abdul Bari, Saleem Ahmed Bhutto, Syed Irfan Raza Arif, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2025)
Objective: To compare the efficacy, safety, and postoperative outcomes of three-port versus four-port laparoscopic cholecystectomy (LC) in patients with acute cholecystitis. Methods: A prospective, randomized controlled trial was conducted involving 170 patients diagnosed with acute cholecystitis. Patients were randomly assigned to undergo either three-port or four-port LC. Demographic data, operative time, postoperative pain (measured by Visual Analog Scale), analgesic requirements, hospital stay duration, and complication rates were recorded and analyzed. Results: The three-port group (n=85) had a mean age of 42.5 years, while the four-port group (n=85) had a mean age of 43.2 years. The male-to-female ratio was 1:2 in both groups. Operative times were comparable between the two groups (mean 45 minutes for three-port vs. 47 minutes for four-port, p=0.35). Postoperative pain scores were significantly lower in the three-port group (mean VAS score 2.1 vs. 3.4, p<0.001). Analgesic requirements were also reduced in the three-port group (mean 120 mg pethidine vs. 180 mg, p<0.01). Hospital stay was shorter in the three-port group (mean 2.3 days vs. 3.1 days, p<0.05). No significant differences were observed in complication rates or conversion to open surgery between the two groups. Conclusion: Three-port laparoscopic cholecystectomy is a safe and effective alternative to the traditional four-port approach for acute cholecystitis, offering benefits in terms of reduced postoperative pain, lower analgesic requirements, and shorter hospital stays without compromising safety or efficacy. Keywords: Three-port laparoscopic cholecystectomy, four-port laparoscopic cholecystectomy, acute cholecystitis, postoperative pain, hospital stay, surgical outcomes.